Geographical Indications As An Alternative To Save The Potential Product Of Micro, Small And Medium Enterprises (MSMEs) In Sragen Regency - Triyono Adi Saputro; Yudho Taruno Muryanto; Suraji Suraji (Fakultas Hukum Universitas Mataram, 2020)
This research was conducted as an effort to analyze the MSMEs’ products of Sragen Regency which have not been known and have the potential to be granted legal protection through geographical indications. This research is an empirical legal research with primary and secondary legal basic materials. The research location was carried out in Kalijambe Sub-district with data collection techniques through literature study and direct interviews with local governments and businessmen in Sangiran. The result of the research is that in Sragen Regency, there is a product which can be categorized as geographical indication and has good prospects for the long term and is able to maintain the reputation of the existing area in Sragen. The product is Sangiran’s fossil stone handicraft, which is a potential superior product to be registered through geographical indications, so that registration with geographical indications can be used as an effort to save potential MSMEs’ products in Sragen Regency by the fossil stone handicrafts in Kalijambe Sub-district. This effort is also a form of legal protection for superior regional products of Sragen Regency in accordance with the mandate of Sragen Regency Regional Regulation Number 3 Year 2013 concerning MSMEs.